Habermas and Ratzinger on the Future of Religion - Welker, Michael (Scottish journal of theology, 2010)
The article investigates the encounter between Joseph Cardinal Ratzinger and Jürgen Habermas in Munich 2004. The event was widely regarded as a conversation about the topic ‘The Pre-Political Moral Foundations of a Liberal State’. It was praised as a dialogue between the ‘personification of the Catholic faith’ and ‘the personification of liberal, individual and secular thought’ with far-reaching consequences. A close analysis of the texts, however, shows that Ratzinger and Habermas think in quite incompatible frameworks with very different concerns. They both share a sceptical attitude towards scientific ideology and they both show a remarkable lack of cultural and political realism. Habermas assumes that civil-societal elites will transform moral concerns into political and legal power. Ratzinger hopes for a revival of natural law tradition which would overcome the ‘pathologies of reason’ and political and religious fanaticism.